EFEKTIVITAS MODEL KOOPERATIF TIPE STAD DALAM MEMBENTUK KARAKTER TOLERANSI PESERTA DIDIK PADA PELAJARAN PPKN - Leonardus Leonardus; Agus Sastrawan Noor; Thomy Sastra Atmaja (Universitas Tanjungpura, 2020)
AbstractThis study is entitled The Effectiveness of the Use of STAD in Cooperative Learning in Shaping Students' Tolerance Character in PPKn Subject Class XI IPS SMA Negeri 7 Pontianak. This study aimed to determine the effectiveness of STAD in shaping students' tolerance character. This study used Experimental study with quantitative research. The independent variable was the study of STAD. The dependent variable was the effectiveness of students' tolerance character. The participants were the students of XI IPS 2 SMA 7 Pontianak. The data collection technique used observation. The analysis included the normality test, t-test, the significance level of 5%, effect size, the calculation process using the SPSS version 16.0 program. The results showed that before applying the STAD, there was an average value of the tolerance character of students 4.64. After being treated with the STAD, there was an average tolerance character of students 6.12. There was an effective use of STAD in cooperative learning in shaping students' tolerance character in PPKn subject for XI IPS 2 SMA Negeri 7 Pontianak. With a significance level of 0,000 or 0,000 <0.05, Ho was rejected. Thus, the tolerance character of students in SMA Negeri 7 Pontianak had 6 of 7 tolerance characters.Keywords: Character Tolerance, Effectiveness, PPKN, STAD Type Cooperative Learning.